Hematological changes in patients with malaria in a tertiary care hospital, Multan, Punjab, Pakistan - Akhter, Naseem; ., Nazishmazari; Asif, Maliha; Khan, Ahmed Raza; Habiba, Umme; Ammar, Tooba (International Journal Of Community Medicine And Public Health, 2021)
Background: Malaria is one of the most common human infections and continues to cause significant morbidity and mortality all over the world. To assess and compare the hematological changes in common types of malaria in our patients. Methods: This observational study included 100 diagnosed malaria patients of Multan Medical and Dental college, Multan both from out patient department (OPD) and in-patient department, between March 2020 and March 2021. The diagnosis of malaria was confirmed by thick and thin film stained with Geimsa’s staining for malaria parasite and plasmodium species and the parasite index (MPI) in some cases. Complete blood counts (CBCs) were performed and WBC differential was done on all cases. Results: The most common type of malarial parasite was Plasmodium vivax followed by Plasmodium falciparum and 89% of the patient had thrombocytopenia, 70 % anemia, 23% had leukopenia and 10% had raised WBC count. The mean parasite load was 1.275±0.629%, 20 % of the cases showed neutropenia, 40 % had lymphopenia and 40 % showed monocytopenia. Of all the cases 15 % had neutrophilia, 8 % had lymphocytosis and 5 % had eosinophilia. Thrombocytopenia was slightly more in P. falciparum (58.69%) than P. vivax (30.18%) cases, p>0.05, whereas there was no significant difference in the incidence of anemia in two groups (34.68% vs 33.82%) with p>0.05. Conclusions: P. vivax is the common malarial parasite in our population. Both P. vivax and P. falciparum can cause marked hematological changes including thrombocytopenia, anemia, lymphopenia and monocytopenia.